ANALISIS STRUKTUR TEKS FABEL SISWA KELAS VII SMP NEGERI 18 MAKASSAR - Ernawati Ernawati; Mayong Mayong; Usman Usman (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2020)
Analysis Structure Fable Texts Students of Grade VII State Junior High School 18 Makassar. This study aims to describe the structure of fable story text in the writing of eighth grade students of SMP Negeri 18 Makassar on aspects of the fable story text content. The data collection techniques in this study were the writing technique of fable story texts. The research data was obtained through assignments by teachers to students, which were done at school. The results showed that. The use of fable story structure written by eighth grade students of SMP Negeri 18 Makassar which included the use of structure (orientation, complications, resolution and koda) found as many as ten fable stories. 1 fable story that does not have a resolution structure, and there are ten fable stories that do not have a koda structure of a total of 20 fable stories.